Mathematics(bca 2nd semester) - Sarkar, Swapan Kumar (Aryan Publishing House, 2020)
Mathematics(bca 2nd semester) / Sarkar, Swapan Kumar. -- Kolkata: Aryan Publishing House, 2020 510 Sa243 No. of Copies : 1